2020
DOI: 10.1016/j.kint.2019.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Cadmium exposure enhances organic cation transporter 2 trafficking to the kidney membrane and exacerbates cisplatin nephrotoxicity

Abstract: Renal accumulation and exposure of cadmium originating from pollution in agricultural land and the prevalence of cigarette smoking remains an unneglectable human health concern. Whereas cadmium exposure has been correlated with increased incidence of a variety of kidney diseases, little is known pertaining to its effect on renal drug disposition and response in patients. Here, we report that cadmium exposure significantly increased the activity of organic cation transporter 2 (OCT2), a critical renal drug tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 53 publications
4
9
0
Order By: Relevance
“…In this study, we firstly confirmed that Cd 2+ exposure led to an increased activity of OCTs as reported recently [ 18 ], while possessing an inhibitory effect on MATEs in HEK293 cells. Then, the mechanism underlying these divergent effects of Cd 2+ exposure on transporter activities was explored.…”
Section: Introductionsupporting
confidence: 89%
See 4 more Smart Citations
“…In this study, we firstly confirmed that Cd 2+ exposure led to an increased activity of OCTs as reported recently [ 18 ], while possessing an inhibitory effect on MATEs in HEK293 cells. Then, the mechanism underlying these divergent effects of Cd 2+ exposure on transporter activities was explored.…”
Section: Introductionsupporting
confidence: 89%
“…The uptake was performed in Krebs-Ringer HEPES (KRH) buffer for OCTs and in K + -based buffer (KBB) for MATEs as previously described [ 11 , 23 ]. As described previously [ 18 ], when applicable, the cells were pre-incubated with Cd 2+ for 20 min to enhance the activities of transporters, if any. Then, the uptake assay was performed in the presence or absence of Cd 2+ .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations